Conceptual semantics a micro-modular approach - Nikanne, Urpo, 1961- (Constructional approaches to language,, 2018)
"In this book, the micro-modular approach known as Tiernet within Conceptual Semantics is introduced. Constructions make up an important part in the approach, but in this approach constructions are considered to be exceptions, licensed links between micro-modules, one of the kinds of symbolic modules in the approach. Similar to construction grammar approaches, the micro-modular approach takes a solid interest in the 'periphery' and thus also studies irregular linking principles like constructions. The book details particulars in the development of generative grammar and the relation of Conceptual Semantics to this development, and then introduces the micro-modular approach and shows its usefulness for the description of language generally by not only using examples from English, but also, and in particular, by applying the micro-modular approach of Conceptual Semantics to data from Finnish"--